Design and Synthesis of Highly Porous Activated Carbons from Sargassum as Advanced Electrode Materials for Supercapacitors. Issue 14 (13th September 2019) - Guo, Feiqiang; Jia, Xiaopeng; Liang, Shuang; Jiang, Xiaochen; Peng, Kuangye; Qian, Lin
Abstract : The synthesis of three-dimensional porous biomass carbon was investigated using sargassum as precursor employing KOH, ZnCl2 and H3 PO4 as the activators for the application as electrode materials for supercapacitors. H3 PO4 activation resulted in the plugging of pore structure due to the formation of crystallized phosphorus, while three-dimensional framework of porous carbons were synthesized applying ZnCl2 and KOH. Compared with ZnCl2 (441.14 m 2 g −1 ), larger surface area was achieved by KOH activation (2486.18 m 2 g −1 ) at 700°C, leading to the significantly better electrochemical performance. The porosity of KOH activated carbon was further improved by adjusting the activation temperature, and a high surface area of 3170.02 m 2 g −1 was obtained by two-step activation of firstly 400°C activation for 45 min and then 800°C for 2 h (KOH-400-800). KOH-400-800 electrode exhibited a high capacitance of 316 F g −1 at 1 A g −1 with good rate capacity (84% retention at 10 A g −1 ) and excellent cycling stability of 99.4% capacitance retention after 5000 cycles. The KOH-400-800 sample also showed a high energy density of 41.67 W h kg −1 and a power density of 320.51 W kg −1 at a current density of 1 A g −1 in the voltage range of 0–1 V.